Factors Related to Adolescent Girls' Attitudes Toward Consuming Rorano Herbal Medicine - Nurkila Suaib; Irawati Umaternate; Asmaryani Hasim (Pascasarjana, Mataram University, 2026)
This study comprehensively identified and analyzed multifaceted factors influencing adolescent girls' attitudes toward consuming Rorano herbal medicine within the Indonesian cultural context. This study aimed to analyze knowledge, interest, cultural, and economic factors related to adolescent girls' attitudes toward consuming Rorano Datang Bulan herbal medicine in the working area of ​​Bahari Berkesan Community Health Center, Ternate City. A cross-sectional, observational analytical design was implemented from July to December, using a structured questionnaire. All adolescent girls aged 12–16 years who were menstruating and consuming Rorano (n=65) were included through total sampling. The majority were aged 12–13 years (52.3%), had parental income below the minimum wage (UMR) (55.4%), and had knowledge and attitudes categorized as